Reconstructing Legal Liability and Division of Authority: Mitigating Mass Poisoning in the Free Nutritious Meal Program - Latemmamala, Andi Fitrah; Fachri, Faiz Ahmad (SIGn Jurnal Hukum, 2025)
The FNM Program is a manifestation of fulfilling citizens’ constitutional rights, currently facing a serious crisis of legitimacy due to the escalation of mass poisoning incidents that have claimed up to 21,254 student victims. This phenomenon demonstrates the failure of administrative control mechanisms that rely solely on Presidential Regulations. The present study aims to critique the ambiguity of legal liability arising from the absence of sanction norms and to reconstruct an integrated law enforcement system. Through doctrinal legal research using statutory and conceptual approaches, this study reveals that Presidential Regulation Number 115 of 2025 suffers from “repressive paralysis” because it is hierarchically prohibited from containing criminal provisions, thereby creating a loophole of impunity for corporate crimes and official maladministration. The absence of legal coercive power leads to technical food safety standards being frequently ignored in pursuit of economic profit. Based on these findings, the present study recommends reconstructing the legal liability system through a dual-layer legislative scheme. At the national level, it urges the initiation of drafting an Academic Paper and a Bill within the National Legislation Program carrying the nomenclature “National Nutrition Fulfillment” as a lex specialis harmonizing severe criminal sanctions, individual/corporate criminal liability, and restitution for victims. At the regional level, it encourages the Regional Government and the Regional House of Representatives to draft an academic study for the formation of a Draft Regional Regulation, to provide preventive-repressive executive authority in the form of administrative sanctions and criminal fines. This synergy between severe punishment at the center and daily supervision in the regions is necessary to restore public trust and guarantee the protection of human rights to safe food.